DEVELOPMENT OF A TRAINING MODEL FOR MAKING KARAWO MOTIF DESIGNS - MUKHLISULFATIH LATIEF; SYAHRUL SYAHRUL; ABDUL MUIS MAPPALOTTENG (Jurnal Vokasi Keteknikan, 2023)
The objectives of this study are to: (1) Produce a training model design for making karawo motif designs for karawo craftsmen, (2) Produce a valid training model for making karawo motif designs, (3) Produce a training model for making karawo motif designs that are practical to use, The development model used in this study is the ADDIE model. The test includes four test stages, namely expert review (content validity), product feasibility testing of training model devices, limited trials, and expanded trials. In the limited trial there were 15 karawo craftsmen involved and for the expanded test there were 30 karawo craftsmen as respondents. Data collection related to the development of training models using interviews. Expert review using Aiken's formula, feasibility test using descriptive statistics, limited trials as well as expanded trials to measure the practicality of the training model. The results showed that (1) This karawo motif design training model product can be used to improve the competence of karawo craftsmen in designing karawo motifs. This model is equipped with (a) Training model book for making karawo motif designs, (b) Karawogen application as one of the supports and tools for karawo craftsmen in making new and more varied karawo motifs, and (c) Training modules for making karawo motif designs, (2) Based on expert analysis, This training model is declared valid which is indicated by (a) The training model book for making karawo motif designs is included in the Very feasible category, (b) Karawogen application is included in the very feasible category, and (c) The training module is included in the very feasible category, (3) Practicality assessment in limited and expanded product trials is included in the practical category.